The association of cariogenic foods consumption frequency on the occurrence of dental caries in children with autism spectrum disorders - Dewi, Chita Sintya; Primarti, Risti Saptarini; Sasmita, Inne Suherna (Padjadjaran Journal of Dentistry, 2023)
ABSTRACTIntroduction: Dental caries is a multifactorial disease that invades the hard tissues of the teeth. Dental caries is among the most common oral manifestations in children with autism spectrum disorders (ASD). ASD is a neurodevelopmental disorder characterized by deficits in social interactions, communication difficulties, and restricted repetitive behavior. ASD children have a higher risk of dental caries due to their difficulty maintaining good oral hygiene and poor diet, such as having a high preference for cariogenic foods. This study aims to analyze the association between cariogenic foods consumption frequency and the occurrence of dental caries in ASD children. Methods: Quantitative study was performed with a cross-sectional design and total sampling techniques on 15 ASD children. Data analysis using Spearman Rank test. Results: This study found (66,7%) of ASD children had low levels of cariogenic foods consumption. Respectively, the ASD children’s deft and DMFT indices were (3.3) and (4.4). A significant value between the frequency of consumption of cariogenic foods and DMFT/deft was (0.297). The level of relationship between the frequency of consumption of cariogenic foods with DMFT/deft is (0.289), indicating a low association. Conclusions: There is no association between cariogenic foods consumption frequency and the occurrence of dental caries in children with ASD. The average indices of DMFT and deft of ASD children are at moderate levels. ASD children have low levels of cariogenic food consumption frequency.Keywords: Autism Spectrum Disorder (ASD), Cariogenic Foods, Dental Caries.